Peran Guru PAI Dalam Pembelajaran Agama Islam Pada Siswa - Sabrina, Ninda; Pahrurroji, Pahrurroji (Prodi Pendidikan Keagamaan Islam, 2024)
The role of the teacher as a teacher is the most popular so far. Teachers are not only required as teachers but at least as educators who educate. Based on the results of a survey conducted by the author at SDN Tanahbaru I Karawang, the role of religious teachers there play a very active role in learning Islamic religious education, resulting in a lot of student interest in Islamic religious studies. This research aims to find out what role teachers at SDN Tanahbaru I have and also to find out the obstacles PAI teachers have in learning the Islamic religion at SDN Tanahbaru I Karawang. This type of research is a type of qualitative field research (field research), namely to strengthen data theoretically and obtain information from informants related to the title. The research subjects namely, subject teachers and students. Data collection techniques used are through observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. The results of the research show that students' interests, talents, abilities, and potentials will not develop optimally without the help of the teacher. In this regard, the teacher needs to pay attention to students individually, because one student and another have very basic differences. The Obstacles in the Role of Islamic Religious Education Teachers in Learning Islamic Religious Education for Students at SDN Tanahbaru I, namely, the lack of several teachers, too many students, and parental support.